2019
DOI: 10.1145/3150974
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Techniques for Sign Language Alphabet Recognition Using Armband Wearables

Abstract: Recent research has shown that reliable recognition of sign language words and phrases using user-friendly and noninvasive armbands is feasible and desirable. This work provides an analysis and implementation of including fingerspelling recognition (FR) in such systems, which is a much harder problem due to lack of distinctive hand movements. A novel algorithm called DyFAV (Dynamic Feature Selection and Voting) is proposed for this purpose that exploits the fact that fingerspelling has a finite corpus (26 alph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Finally, we proposed a novel automatic segmentation technique for continuous recognition that can automatically annotate eating action. This technique can also be potentially used for other poly-componential gesture-based applications such as American Sign Language Recognition [28][29][30]. This is an important finding for future work.…”
Section: Discussionmentioning
confidence: 96%
“…Finally, we proposed a novel automatic segmentation technique for continuous recognition that can automatically annotate eating action. This technique can also be potentially used for other poly-componential gesture-based applications such as American Sign Language Recognition [28][29][30]. This is an important finding for future work.…”
Section: Discussionmentioning
confidence: 96%
“…In the study of Halawani (2008), Fajardo et al, (2009) and Paudyal et al, (2019), it is shown that teaching and learning sign language requires good ICT facilities to attract the individuals to learn. The availability of ICTs in the teaching and learning of sign language can enhance students' skills and quality (Paudyal et al, 2019). A conducive environment can be formed if the sign language courses have adequate ICT facilities (Chai et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…According to Halawani (2008), Fajardo et al (2009) and Paudyal et al (2019), they also said that teaching and learning sign language requires good ICT facilities to attract individuals to learn them. In addition, teaching and learning sign language using ICT can enhance students' skills and quality (Paudyal et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Wearable IoT devices have been studied extensively due to their form factor and cost benefits. Researchers have proposed sensor networks, gesture-based control, health monitoring, and activity monitoring as potential applications of IoT devices [16][17][18][19][20][21][22]. Gesture recognition using wearable devices has received significant attention due to its applications in human-computer interaction, gesture-based control, and virtual reality [23][24][25][26].…”
Section: Related Workmentioning
confidence: 99%